LMI optimization problem of delay-dependent robust stability criteria for stochastic systems with polytopic and linear fractional uncertainties - Balasubramaniam, Pagavathigounder; Lakshmanan, Shanmugam; Rakkiyappan, Rajan (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies an LMI optimization problem of delay-dependent robust stability criteria for stochastic systems with polytopic and linear fractional uncertainties. The delay is assumed to be time-varying and belong to a given interval, which means that lower and upper bounds of this interval time-varying delay are available. The uncertainty under consideration includes polytopic-type uncertainty and linear fractional norm-bounded uncertainty.
Keywords: delay-dependent stability; linear matrix inequality; Lyapunov-Krasovskii functional; stochastic systems